-(7y+2)-(6y-4)=-2

Simple and best practice solution for -(7y+2)-(6y-4)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7y+2)-(6y-4)=-2 equation:


Simplifying
-1(7y + 2) + -1(6y + -4) = -2

Reorder the terms:
-1(2 + 7y) + -1(6y + -4) = -2
(2 * -1 + 7y * -1) + -1(6y + -4) = -2
(-2 + -7y) + -1(6y + -4) = -2

Reorder the terms:
-2 + -7y + -1(-4 + 6y) = -2
-2 + -7y + (-4 * -1 + 6y * -1) = -2
-2 + -7y + (4 + -6y) = -2

Reorder the terms:
-2 + 4 + -7y + -6y = -2

Combine like terms: -2 + 4 = 2
2 + -7y + -6y = -2

Combine like terms: -7y + -6y = -13y
2 + -13y = -2

Solving
2 + -13y = -2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -13y = -2 + -2

Combine like terms: 2 + -2 = 0
0 + -13y = -2 + -2
-13y = -2 + -2

Combine like terms: -2 + -2 = -4
-13y = -4

Divide each side by '-13'.
y = 0.3076923077

Simplifying
y = 0.3076923077

See similar equations:

| (x-3)/x^2 | | 16+32+x=72 | | 2x+71=4x+51 | | 4x+9y=106 | | (x+2.8)(37.2-2x)=50 | | 3x(3)-78=144 | | 6x-15=4x+13 | | (a-1)(a-5)=0 | | 8t^2-5t-25=0 | | 4n+12+n=-3n+17 | | 8.2x+1.5=21.5-1.8x | | 2t^2-6t+18=0 | | 5-8x+7=-9x-9-5 | | 2b/5-1/0=-1/2 | | x^2+30x+117=0 | | x-8.9=-4.7 | | 10b^2-18b-36=0 | | 15p+p=7-12 | | p+39=14 | | ln(5x+4)=5 | | 5(k-8)-2(k-1)=2k-9 | | 4.2z-1.3=3.7z+3.2 | | y=-3/7*8.6154+3 | | x+(x+6)=44 | | 24x-6=24x+8 | | 3y^2-7y=3 | | 135-(4.7)x=0 | | 12-12n=-43 | | x/3+3=x/5-91/3 | | -x^2+82=0 | | 3x=3x-24 | | k^-4/2 |

Equations solver categories